A cluster randomized controlled trial for the Evaluation of routinely Measured PATient reported outcomes in HemodialYsis care (EMPATHY): a study protocol - Jeffrey A. Johnson; Fatima Al Sayah; Robert Buzinski; Bonnie Corradetti; Sara N. Davison; Meghan J. Elliott; Scott Klarenbach; Braden Manns; Kara Schick-Makaroff; Hilary Short; Chandra Thomas; Michael Walsh (BMC, 2020)
Abstract Background Kidney failure requiring dialysis is associated with poor health outcomes and health-related quality of life (HRQL). Patient-reported outcome measures (PROMs) capture symptom burden, level of functioning and other outcomes from a patient perspective, and can support clinicians to monitor disease progression, address symptoms, and facilitate patient-centered care. While evidence suggests the use of PROMs in clinical practice can lead to improved patient experience in some settings, the impact on patients' health outcomes and experiences is not fully understood, and their cost-effectiveness in clinical settings is unknown. This study aims to fill these gaps by evaluating the effectiveness and cost-effectiveness of routinely measuring PROMs on patient-reported experience, clinical outcomes, HRQL, and healthcare utilization. Methods The EMPATHY trial is a pragmatic multi-centre cluster randomized controlled trial that will implement and evaluate the use of disease-specific and generic PROMs in three kidney care programs in Canada. In-centre hemodialysis units will be randomized into four groups, whereby patients: 1) complete a disease-specific PROM; 2) complete a generic PROM; 3) complete both types of PROMs; 4) receive usual care and do not complete any PROMs. While clinical care pathways are available to all hemodialysis units in the study, for the three active intervention groups, the results of the PROMs will be linked to treatment aids for clinicians and patients. The primary outcome of this study is patient-provider communication, assessed by the Communication Assessment Tool (CAT). Secondary outcomes include patient management and symptoms, use of healthcare services, and the costs of implementing this intervention will also be estimated. The present protocol fulfilled the Standard Protocol Items: Recommendations for Intervention Trials (SPIRIT) checklist. Discussion While using PROMs in clinical practice is supported by theory and rationale, and may engage patients and enhance their role in decisions regarding their care and outcomes, the best approach of their use is still uncertain. It is important to rigorously evaluate such interventions and investments to ensure they provide value for patients and health systems. Trial registration Protocol version (1.0) and trial registration data are available on www.clinicaltrials.gov , identifier: NCT03535922 , registered May 24, 2018.